The impact of glutaraldehyde on the characteristics of bovine hydroxyapatite-gelatin based bone scaffold as gentamicin delivery system - Aniek Setiya Budiatin, - (Walter de Gruyter GmbH, 2021)
Objectives Biomaterials are widely used as drug delivery systems targeting bone tissue, such as to treat bone infectious disease. However, the addition of drugs to biomaterials weakens their mechanical properties. Crosslinkers are compounds that improve the mechanical properties of biomaterials. This study aims to determine the effect of glutaraldehyde (GTA) as a crosslinker on the characteristics of bovine hydroxyapatite-gelatin-based bone scaffold with gentamicin as antibiotics (BHA-GEL-GEN-GTA).